Advantageous of Volunteerism Values for Indonesian Community and Neighbourhoods - Adha, Muhammad Mona (International Journal of Community Service Learning, 2019)
The skills and participation of citizens are urgently needed for progress and prosperity in the community. Volunteerism opens opportunities for each individual to participate and contribute based on the knowledge and experience he has had in previous voluntary activities. Qualitative research implemented on this research, and ethnography method to explore the cultural background and young people engagement. Young people participation in voluntary activity has a positive impact on building community solidarity that strengthens togetherness and kinship. Sympathy and empathy are strengths in increasing individual motivation in voluntary activities. Volunteerism creates space for interaction and communication between individuals involvement in social activities. Social capital that runs well will bring about social welfare, this can be started from the involvement of individuals called active citizenship. The implications from the research are: 1) community need some positive activity and opportunity to engage; 2) the more young people engage with the social activities the more they are trained and experienced.